If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -1(b + -3) = 56 Reorder the terms: 6b + -1(-3 + b) = 56 6b + (-3 * -1 + b * -1) = 56 6b + (3 + -1b) = 56 Reorder the terms: 3 + 6b + -1b = 56 Combine like terms: 6b + -1b = 5b 3 + 5b = 56 Solving 3 + 5b = 56 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5b = 56 + -3 Combine like terms: 3 + -3 = 0 0 + 5b = 56 + -3 5b = 56 + -3 Combine like terms: 56 + -3 = 53 5b = 53 Divide each side by '5'. b = 10.6 Simplifying b = 10.6
| (8x-17)+3= | | k+2k=65 | | 252+4x=284 | | 2y/y-1=5/y+(10-8y)/(y^2-y) | | 5i/(6-2i) | | 37-n=12 | | -18=-3z | | 2x+4+3x=24 | | 12x+25=200 | | 12+n=17 | | 180-x=3(x-2) | | 11+5=16 | | -3/8-(-1/5)-(-7/3) | | 3(-2+3n)=-7n-6 | | -4y=4 | | -7(a+5)=-40-8a | | -36-7x=6(4-4x)+5x | | 4-8x=5(4x+6)-2x | | 10+n/15=12 | | 12+3y=84 | | -62=5-3(1-3x) | | 4+5(8+6m)=-22+8m | | 24+2x=2(2x+7) | | 5x^3+15x^2+12x+36=0 | | 1-8(5k-5)=-33-3k | | -3-3b=-(-2+4b) | | 8/5-2=-13 | | 8+7r=-8(r-1) | | -6v-11=4(-2v+6)-1 | | 4.5x-1.5=12 | | -12+4p=-p+3p | | 0=x^4-2x^3-4x^2+2x+3 |